Séparation, annexion, et fédéralisme : au-delà des préceptes normatifs usuels - Carter, Richard (L'Actualité économique)

(untitled) (HEC Montréal, 1983)
AbstractThe author uses a Public Choice approach to analyze the evolution of the political structures of Canadian society and the options facing Canadian society today. The insights provided by a positive approach as opposed to the traditional normative approach are discussed. The records of economic and political history are used to validate the insights provided by this economic approach.